Konsepsi Pengembangan Kemampuan Kepemimpinan Pendidikan Islam - Zaenal Arifin; Sulistyorini Sulistyorini (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
The writing of this article aims to explain the conception of leadership and the development of leadership capabilities in Islamic education institutions both formal and non-formal. Leaders are an important element in the process of managing educational institutions, for that leader in Islamic educational institutions are expected to continue to be able to develop their abilities. To develop their abilities, at least a leader must know the potential associated with the ability of the leader and know how to develop it.